PERAN KEPALA SEKOLAH DASAR DALAM MEMPERSIAPKAN SUMBER DAYA PENDIDIK MENGHADAPI IMPLEMENTASI KURIKULUM 2013 - Badarudin, Badarudin (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
School principals as leaders in primary schools can be a good manager of school progress in the future as well designer. The principal's role is very important because in the hands of the principal policies will progress the school is located. Factors supporting the achievement of a program created by the principal, the teacher's role as an educator as a resource executing the implementation of curriculum 2013, would require the improvement and enhancement of professionalism. Principal's role in preparing resource educator (teacher) facing the implementation of the curriculum in 2013 as a planner and developer in providing a school policy is to increase learning in terms of services, the concept of a credible form of learning that applies the concept of thematic scientific approach, foster harmonious school climate and culture character that can be run in a conducive learning, academic educators increase professionalism through education and training, and instilling cohesion and cooperation among stakeholders in building and developing a school program.